Geographical locational knowledge as an indicator of children's views of the world: research from Sweden and Australia. Issue 1 (2nd January 2016) - Reynolds, Ruth; Vinterek, Monika
Abstract : Children's locational knowledge is often used to clarify underlying conceptual understandings of the world in which they live. Although there has been some exploration of how European children view their world there is little recent research on Scandinavian children's knowledge and associated perceptions of the wider world, or about Australian children's views. Coming from opposite parts of the globe it could be expected that children from Sweden and Australia would view the world in a very different manner. This study compared children's knowledge of countries in the world from comparable schools in both nations and found the expected influence of local geographic knowledge and social and economic place in the world on their skills and knowledge. They were influenced by their national space. However, media and popular culture also impacted on their views on the world and this impact was quite similar between the two nations.